1999
DOI: 10.1021/bi990633u
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Oxidation in Photosystem II

Abstract: The oxidation of carotenoid upon illumination at low temperature has been studied in Mn-depleted photosystem II (PSII) using EPR and electronic absorption spectroscopy. Illumination of PSII at 20 K results in carotenoid cation radical (Car+*) formation in essentially all of the centers. When a sample which was preilluminated at 20 K was warmed in darkness to 120 K, Car+* was replaced by a chlorophyll cation radical. This suggests that carotenoid functions as an electron carrier between P680, the photooxidizabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
238
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(272 citation statements)
references
References 29 publications
28
238
6
Order By: Relevance
“…Taking G Х 2 nS (the largest conductance measured for Car with 9 double bonds under oxidizing potential) (Fig. 3a Middle) yields k et ϭ 5.6 ϫ 10 6 s Ϫ1 or ϭ 0.18 s. Both time scales are significantly smaller than that assumed for electron transfer from Q A Ϫ to P 680 ϩ via ␤-carotene in photosystem II (200 s to 1 ms) (1,30), indicating that the electron transfer is not limited by the transfer across the Car but more likely by other steps in the photoprotection mechanism. Additionally, it is likely that electron transfer in our system involves ballistic tunneling of many electrons as opposed to consecutive oxidation and reduction for the transfer of each electron.…”
Section: Discussionmentioning
confidence: 95%
“…Taking G Х 2 nS (the largest conductance measured for Car with 9 double bonds under oxidizing potential) (Fig. 3a Middle) yields k et ϭ 5.6 ϫ 10 6 s Ϫ1 or ϭ 0.18 s. Both time scales are significantly smaller than that assumed for electron transfer from Q A Ϫ to P 680 ϩ via ␤-carotene in photosystem II (200 s to 1 ms) (1,30), indicating that the electron transfer is not limited by the transfer across the Car but more likely by other steps in the photoprotection mechanism. Additionally, it is likely that electron transfer in our system involves ballistic tunneling of many electrons as opposed to consecutive oxidation and reduction for the transfer of each electron.…”
Section: Discussionmentioning
confidence: 95%
“…As hypothesized by Schelvis et al (1994) the peripheral Chls coordinated by the D1-H118 and D2-H117 residues are sufficiently far removed (approximately 30 Å) from the Chl special pair (P680) to reduce the likelihood of their direct oxidation by P680 ϩ . Consistent with this prediction, it has been shown that Car radicals are generated under cryogenic conditions that lead to the photo-accumulation of Chl Z ϩ suggesting that Car may participate in Chl Z oxidation (Hanley et al, 1999). Chl Z ϩ subsequently is reduced by Cyt b 559 (Buser et al, 1992 Shigemori et al, 1998).…”
mentioning
confidence: 87%
“…This electron transfer cycle includes plastoquinone bound at the B binding site (Q B ), Cyt b 559 , Chl Z (the redox active Chl monomer coordinated by either the D1-H118 or D2-H117 residue), possibly (Car) carotenoid, and the primary donor, P680 ϩ (Koulougliotis et al, 1994;Noguchi et al, 1994;Hanley et al, 1999;Vrettos et al, 1999). Under high-light intensities, both P680 ϩ and doubly reduced Q A may accumulate leading to damage and turnover of the D1 protein (photo-inhibition; Chen et al, 1992;Andersson and Barber, 1996;Napiwotzki et al, 1997;Gadjieva et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Carotenoids also may act as stabilizers of protein structure and facilitators of the assembly of pigment-protein complexes, [13][14][15] as regulators of energy flow, 6,[15][16][17][18][19][20][21] or as redox cofactors. [22][23][24][25] The most well-known naturally occurring carotenoid, -carotene, is a C 40 hydrocarbon with terminal isoprenoid rings and eleven π-electron conjugated carbon-carbon double bonds. Other naturally occurring carotenoids often contain functional group substitutions along the polyene chain and on the isoprenoid terminal rings.…”
Section: Introductionmentioning
confidence: 99%